Use of chitosan bandage to prevent fatal infections developing from highly contaminated wounds in mice - Burkatovskaya, Marina (2006)
HemCon(®) bandage is an engineered chitosan acetate preparation used as a hemostatic control dressing, and its chemical structure suggests that it should also be antimicrobial. We tested its ability to rapidly kill bacteria in vitro and in mouse models of infected wounds. We used the Gram-negative species Pseudomonas aeruginosa and Proteus mirabilis and the Gram-positive Staphylococcus aureus that had all been stably transduced with the entire bacterial lux operon to allow in vivo bioluminescence imaging. An excisional wound in Balb/c mice was inoculated with 50–250 million cells followed after 30 min by application of HemCon bandage, alginate sponge bandage, silver sulfadiazine cream or no treatment. HemCon was more adhesive to the wound and conformed well to the injury compared to alginate. Animal survival was followed over 15 days with observations of bioluminescence emission and animal activity daily. Chitosan acetate treated mice infected with P. aeruginosa and P. mirabilis all survived while those receiving no treatment, alginate and silver sulfadiazine demonstrated 25–100% mortality. Chitosan acetate was much more effective than other treatments in rapidly reducing bioluminescence in the wound consistent with its rapid bactericidal activity in vitro as well as its light-scattering properties. S. aureus formed only non-lethal localized infections after temporary immunosuppression of the mice but HemCon was again more effective in reducing bioluminescence. The data suggest that chitosan acetate rapidly kills bacteria in the wound before systemic invasion can take place, and is superior to alginate bandage and silver sulfadiazine that may both encourage bacterial growth in the short term.